Species-Specific Responses of Root Morphology of Three Co-existing Tree Species to Nutrient Patches Reflect Their Root Foraging Strategies - Yang, Zhenya; Zhou, Benzhi; Ge, Xiaogai; Cao, Yonghui; Brunner, Ivano; Shi, Jiuxi; Li, Mai-He (Frontiers in Plant Science, 2021)
Root foraging strategies of plants may be critical to the competition for nutrient resources in the nutrient patches, but little is known about these of co-existing tree species in subtropical regions. This study aimed to elucidate root foraging strategies of three co-existing tree species in nutrient heterogeneous soils by exploring their root distribution, root morphology, photosynthates allocation and nutrient accumulation. Seedlings of the three tree species [moso bamboo (Phyllostachys edulis), Chinese fir (Cunninghamia lanceolata), and masson pine (Pinus massoniana)] were grown for 8months under one homogeneous soil [uniform nitrogen (N) plus phosphorus (P)] and three heterogeneous soils (localized N supply, localized P supply, or localized N plus P supply). The biomass, root morphological parameters (i.e., root length and root surface area), specific root length (SRL), non-structural carbohydrates (NSCs, i.e., mobile sugar and starch) in roots, total N and total P of plants were measured. The plasticity and distribution of root system were analyzed by calculating the root response ratio (RRR) and root foraging precision (FP), respectively. The results are as follows (i) Chinese fir tended to forage more N by promoting root proliferation in the N-rich patch, while root proliferation of bamboo and pine did not change. For P, bamboo absorbed more P by promoting root proliferation in the P-rich patch. The total P content of Pine and Chinese fir under localized P supply treatment remain the same despite the fact that the root length in the P-rich patch and the FP increased. (ii) Chinese fir foraged more N by increasing root length and decreasing SRL in the NP-rich patch; bamboo foraged more N and P by increasing root length and SRL in the NP-rich patch. The FP and foraging scale (FS) of both bamboo and Chinese fir were significantly improved under localized N plus P treatment. (iii) The concentrations of NSC were positively correlated with root morphological plasticity for moso bamboo and Chinese fir. Our results indicated that higher morphological plasticity is exhibited in moso bamboo and Chinese fir than masson pine in nutrient heterogeneous soils, allowing them to successfully forage for more nutrients.